Teachers With Special Needs. De-Psychiatrization of Children in Schools - Batstra, Laura; van Roy, A.C. Marieke; Thoutenhoofd, Ernst D. (Frontiers in Sociology, 2021)
Psychiatrization not only affects adults. Ever more children in Western countries are being diagnosed with a mental disorder of behavior, such as ADHD. Children may often be labelled with the best intentions, for example in order to be able to provide them with suitable care and guidance. However, this labelling can have exclusionary effects and often entails the consequence that important discussion about contextual factors that give rise to (the perception of) unwelcome behavior or academic underperformance rarely, if at all, takes place. In this article we contend that although children are of central concern to schools and the design of pupils’ education, it is important not to make pupils the owner of problems that arise. It is therefore high time that a far more critical normative stance towards inclusive education is taken, in which the presently widespread biomedical approach that ‘disorders’ individual children is met with a school community response that focuses instead on the special need for additional capacity that teachers and schools have in meeting (perceived) unwelcome behaviors and emotions, and/or related academic underperformance. We argue that teaching should not set out to remedy individual diagnoses, and that teachers should instead be supported to extend their professional competence to the benefit of all pupils.